Toward an ecological civilization: Mass comprehensive ecotourism indications among domestic visitors to a Chinese wetland protected area - Shi, Fangfang; Weaver, David; Zhao, Yanzhi; Huang, Ming-Feng; Tang, Chuanzhong; Liu, Yang (Tourism management (1982), 2019)
Large-scale park-visitor symbiosis remains an aspiration despite the need for new models to address the challenges of managing contemporary protected area systems. A survey of 1050 visitors to the Red Beach National Scenic Corridor in Northeast China, however, indicates a latent potential, with 36.0% qualifying as “enthused ecotourists” and 32.4% as “ecotourists” based on claimed adherence to basic ecotourism characteristics. Another 17.2% are “hands-on greens” also amenable to participation in on-site park enhancement activities but neutral about nature learning. “Ambivalents” account for the remaining 14.4% of the sample. High overall proclivity to participate, report misbehavior, and behave in a more environmentally responsible manner as a result of their Red Beach visit constitutes a basis for mass comprehensive ecotourism that can achieve park-visitor symbiosis and contribute significantly to the creation of an ecological civilization, as long as attendant strategies incorporate distinctive Chinese tendencies in ecotourism and outdoor recreation. •There is strong latent potential for mass comprehensive ecotourism in Chinese protected areas.•“Enthused ecotourists” and “ecotourists” account for over two-thirds of sampled park visitors.•Over 85% of sampled visitors are willing to participate in on-site enhancement activities.•Resultant strategies must hybridize Chinese and Western theory and behavior.•Results show the potential for park visitation to contribute to an ecological civilization.